Knowledge and attitude toward human immunodeficiency virus infection and acquired immunodeficiency syndrome among ayurveda medical students: A single institute experience - Himel Mondal; Shaikat Mondal; Chayan Baidya (Medical Journal of Dr. D.Y. Patil University, 2017)
Background: Human immunodeficiency virus (HIV) infection and acquired immunodeficiency syndrome (AIDS) are global health issue with estimated 21.17 lakhs infected people living with HIV/AIDS (PLHIV) in 2015 in India. Ayurveda doctors are working in different health settings especially in rural India. Adequate knowledge about HIV/AIDS and positive attitude toward PLHIV are desired in treatment and counseling of HIV/AIDS patients. Aim: The aim of the study was to evaluate the level of knowledge about HIV/AIDS and attitude toward PLHIV among Ayurveda medical students. Materials and Methods: A cross-sectional study was conducted with 151 Bachelor of Ayurveda Medicine and Surgery (B.A.M.S.) students of different years of study. A pretested and validated self-administered questionnaire was used as survey instrument. Responses were recorded in “Yes,” “No,” and “Don't Know” tick box. Responses were scored, analyzed, and expressed in percentage, mean and standard deviation. One-way analysis of variance and Pearson's correlation were used according to necessity with α = 0.05. Results: Survey response rate was 91%. Seventy-four percent students had basic knowledge about HIV/AIDS. Correct knowledge about disease transmission was found in 66% students. Positive attitude was found in 51% students. Mean knowledge score of four groups of student according to year of the study was significantly (P < 0.05) different. There was no correlation (P > 0.05, insignificant r) between knowledge and attitude score. Conclusion: B.A.M.S students have basic knowledge about HIV/AIDS with relatively less knowledge about transmission of HIV. Knowledge increases with increase in year of the study. Increase in knowledge is not an indicator of positive attitude toward PLHIV.